Generation of Hierarchical Porosity in Metal–Organic Frameworks by the Modulation of Cation Valence - Qi, Shi‐Chao; Qian, Xin‐Yu; He, Qiu‐Xia; Miao, Kang‐Jing; Jiang, Yao; Tan, Peng; Liu, Xiao‐Qin; Sun, Lin‐Bing (Angewandte Chemie International Edition, 2019)
Hierarchically porous metal–organic frameworks (HP‐MOFs) have attracted great attention owing to their advantages over microporous MOFs in some applications. Despite many attempts, the development of a facile approach to generate HP‐MOFs remains a challenge. Herein we develop a new strategy, namely the modulation of cation valence, to create hierarchical porosity in MOFs. Some of the CuII metal nodes in MOFs can be transformed into CuI via reducing vapor treatment (RVT), which partially changes the coordination mode and thus breaks coordination bonds, resulting in the formation of HP‐MOF based on the original microporous MOF. Both the experimental results and the first‐principles calculation show that it is easy to tailor the amount of CuI and subsequent hierarchical porosity by tuning the RVT duration. It is found that the resultant HP‐MOFs perform much better in the capture of aromatic sulfides than the original microporous MOF. Making the cut: Some of CuII nodes in the metal–organic framework (MOF) HKUST‐1 can be transformed into CuI by a reducing vapor treatment (RVT). This treatment partially changes the coordination mode of the Cu nodes and thus breaks coordination bonds, resulting in the formation of hierarchical pores from the original microporous HKUST‐1.